Calvaria critical-size defects in rats using piezoelectric equipment: a comparison with the classic trephine. Issue 7 (July 2020) - Senos, R.; Hankenson, K.D.
Highlights: 1) Creating large segmental defect in rat calvaria using Piezosurgery is safer than trephine method; 2) There is no increase of bone formation rate on calvaria defect (both in Piezo and trephine technique) after 45 days; 3) The bone regeneration rate using Piezosurgery technique to produce segmental defect is equivalent to trephine technique; 4) Piezosurgery technique is more reproducible than trephine, due to low standard deviation results in new bone formation; 5) Trephine technique is faster to perform than Piezosurgery technique. Abstract: Calvarial critical-size defects in rats are used to study regeneration of both craniofacial bone and long-bones. For decades, the trephine technique has been used with no notable refinements in the procedure. The use of piezoelectric surgical equipment has increased in human clinical oral and maxillofacial surgery, neurosurgery, traumatology, and orthopedics, because the devices are easy to handle, and can cut bone without damaging sensitive soft tissues such as blood vessels, nerves, and membranes. This study evaluated and compared the surgical technique and bone regeneration process between a traditional hand-drill trephine and piezoelectric equipment in a critical-size calvaria defect in a rat model. Thirty SD male rats were randomly divided into two groups and had either a 7.9mm diameter circular defect created with trephine or a 7.0mm square defect using the piezoelectric device, both creating 49 mm2 defect areas. MicroCT and histology were performed at 45 and 75d after surgery. While trephine surgeries were performed faster than piezoelectric (25.5 minutes vs 38.5 minutes), the rate of complications was much higher, with 36% of trephine rats taking 20 minutes to achieve hemostasis. Although the extent of new bone formation was similar between the two surgical groups, the piezoelectric technique resulted in 50% less variability. No additional new bone formation was observed from 45 to 75d in both techniques. Piezoelectric technique represents a refined and more reproducible technique for calvarial defect generation in comparison to classic trephine methods.